EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SECARA DARING SMA ISLAM NGORO JOMBANG - Arif Rahman Hakim; Ahmad Budiyono; Mochamad Halim Wardana (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2022)
Education is a process in order to influence students so that they can adapt as best they can to their environment and cause changes in themselves to function properly in community life. Students can grow and develop in changing themselves well in an educational institution, namely through the teaching process. This study aims to determine the effectiveness of learning Islamic Religious Education online at SMA Islam Ngoro Jombang. This study used a qualitative approach. The data collection techniques were observation, interviews, and documentation. The results of this study indicate that the application of online Islamic Religious Education learning has been going well. In the process of implementing online Islamic Religious Education learning, there are the following steps: First, preparation, determining learning materials, explaining learning objectives and competencies achieved, and making an online learning schedule. Second, implementation, providing material and a problem to be studied and solved, guiding and maintaining an online learning atmosphere, presenting learning outcomes, evaluating and collecting settlement results. Third, evaluation of learning outcomes by providing input related to the online learning process of Islamic Religious Education.